The Triple Star AR Aurigae - Mikulášek, Z.; Žižňovský, J.; Zejda, M.; Zverko, J.; Hubrig, S.; Krtička, J.; Dubovský, P. A.; Gazeas, K.; Zoła, S.; Ogłoza, W.; Albayrak, B.; Chrastina, M.; et al. (Magnetic Stars, 2011)
New period of the third body in the system of the eclipsing HgMn binary star AR Aur was derived based on new photoelectric and CCD observations.